Data supporting the growth/no growth interface of Zygosaccharomyces bailii in simulated acid sauces - Zalazar, Aldana Lourdes (2018)
This article contains experimental data, images and methods for the growth/no growth interface of Zygosaccharomyces bailii in simulated acid sauces. Mentioned data are related to the research article “Modeling growth/no growth interface of Zygosaccharomyces bailii in simulated acid sauces as a function of natamycin, xanthan gum and sodium chloride concentrations” (Zalazar et al., 2018) [1]. The growth was assessed colorimetrically by using 2-(4-iodophenyl)-3-(4-nitrophenyl)-5-phenyl-2H-tetrazolium chloride and 2-methoxy-1,4-naphthoquinone as detection reagents. Furthermore, yeast growth was confirmed by plate count.